2014
DOI: 10.1111/nph.12691
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination and rising atmospheric CO2 concentration: a meta‐analysis of parental and direct effects

Abstract: SummaryPlant regeneration from seed is largely governed by germinability and speed of germination. These fitness components have received considerably less attention in CO 2 research relative to studies of vegetative or reproductive output responses. Moreover, the limited literature has not been rigorously examined for generalizable patterns of responses and/or potential mechanisms. We used a meta-analytic approach to summarize literature results of seed germination characteristics in response to parental CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 134 publications
(195 reference statements)
1
10
0
1
Order By: Relevance
“…Impacts of CO 2 enrichment, warming, and the combination of these two on seed germination were consistent across a wide range of temperature regimes (Table 4). Seed germination response to warming and/or elevated CO 2 concentrations is species specific, agreeing with previous studies (Huxman et al , 1998; Williams et al , 2007; Gao et al , 2012; Marty and BassiriRad, 2014). Future climate condition (CT) favoured seed germination of C 4 grass B. gracilis but not the three C 3 species in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Impacts of CO 2 enrichment, warming, and the combination of these two on seed germination were consistent across a wide range of temperature regimes (Table 4). Seed germination response to warming and/or elevated CO 2 concentrations is species specific, agreeing with previous studies (Huxman et al , 1998; Williams et al , 2007; Gao et al , 2012; Marty and BassiriRad, 2014). Future climate condition (CT) favoured seed germination of C 4 grass B. gracilis but not the three C 3 species in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The maternal effect of various seed traits including seed size was shown in many other crops to be correlated with parental environmental effects (e.g. availability of light, temperature, water, and nutrients) and cytoplasmic effects [39] [40] . Based on the contribution ratio of GCA variance and correlation between heterosis levels and GCA of parents, paternal parent contributed more than maternal parent for SY, which provided valuable information for SY improvement in hybrid breeding of rapeseed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, higher biomass production under CO 2 enrichment may result in more seeds because more resources can be allocated to reproduction (Jablonski et al., ). This effect is enhanced by changes in resource acquisition due to elevated CO 2 , which also supports higher seed production (Marty & BassiriRad, ).…”
Section: Discussionmentioning
confidence: 73%
“…Still, a closer look at the effects of the CO 2 treatment revealed several significant effects, such as higher seed densities under eCO 2 . Different studies have shown that eCO 2 affects seed production and seed germination in grassland (Bloor et al., ; Edwards et al., ; Jablonski et al., ; Marty & BassiriRad, ).…”
Section: Discussionmentioning
confidence: 99%